Return on investment of the international potato center-led seed system interventions in Malawi - Feukeng, F.T.; Otieno, D.J.; Rajendran, S.; Demo, P.; Parker, M. (Wiley, 2024)
With declining funding in agricultural research and development coupled with tremendous pressure from different stakeholders, it is now essential for research institutes to demonstrate the return on investments in projects they implement. In response to the above need, this study evaluated the return on investment of seed sector interventions implemented by the International Potato Center in Malawi with the financial support of 3.425 million Euros from the Irish Aid from 2007 to 2017. The project interventions evaluated in this study were: seed selection, seed multiplication technologies and potato (Solanum tuberosum) varieties. The study used the economic surplus model to measure monetary benefits realized by the project, while a cost-benefit analysis was employed to estimate the return on investment. Results revealed positive returns on donors’ investments over the project's lifespan. The net project worth was estimated at US$ 66.6 million when net benefits are discounted by 6% and US$ 71.8 million when net benefits are discounted by 12% over 23 years project benefit lifespan (2007 to 2030). The basic return on investment found a US$ 6 to US$ 8 return considering a 6% and 12% discount rate, respectively for every dollar invested. Despite these positive results, further investments are needed in the seed production system for the early seed generations. Effective regulatory interventions on seed quality assurance and continuous awareness creation efforts are required to encourage farmers to use the best seed production methods.